PEMANFAATAN WEARABLE DEVICES DALAM PEMANTAUAN PASIEN DIABETES MELLITUS TIPE 2 DI INDONESIA: SCOPING REVIEW - Akri, Yusnita Julyarni; Adelia, Donna Dwinita; Yunamawan L.S, Donny; Irawan, Yanuar Hadi (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
Type 2 diabetes mellitus (DMT2) is one of the chronic diseases with a high prevalence in Indonesia. The main challenges in patients are limited self-monitoring, low adherence to therapy, and early detection of complications. Wearable devices, such as smartwatches and health sensors, are starting to be used globally to monitor the condition of DMT2 patients, but the evidence of their use in Indonesia is still not comprehensively mapped. Identify and map the literature related to the use of wearable devices in monitoring DMT2 patients in Indonesia. This study is a scoping review that follows the framework of the Arksey & O'Malley methodology. Literature searches were conducted on PubMed, Scopus, ScienceDirect, Google Scholar, and Garuda with a range of 2013–2025. Keywords include "wearable devices", "smartwatch", "diabetes mellitus type 2", "Indonesia", and "self-monitoring". The included articles are publications in English or Indonesian that discuss the use of wearable devices in DMT2 patients in Indonesia. Of the 312 articles identified, 5 met the inclusion criteria. The most widely used wearable devices are smartwatches with physical activity monitoring, non-invasive glucose levels, and sleep pattern detection. Most studies were limited trials and observational studies. The results show wearable devices can improve patient adherence to self-management, lower HbA1c levels, and provide real-time data for healthcare workers. However, the main barriers are cost affordability, limited integration with electronic medical records, and patient digital literacy. Wearable devices have the potential to support monitoring of DMT2 patients in Indonesia, but further research with longitudinal design and large-scale clinical trials is still needed. Integration into the national digital health system is also important to expand its utilization.